Making Change: Attempts to Reduce or Stop Gambling in a General Population Sample of People Who Gamble - Hodgins, David C.; Williams, Robert J.; Belanger, Yale D.; Christensen, Darren R.; El-Guebaly, Nady; McGrath, Daniel S.; Nicoll, Fiona; Shaw, Carrie A.; Stevens, Rhys M. G. (Frontiers in Psychiatry, 2022)
Objective This study examined past year attempts to reduce or quit gambling among people who gamble generally and those with gambling problems specifically. Methods Regular gamblers recruited from an online panel (N = 10,054) completed a survey of gambling, mental health and substance use comorbidity and attempts to reduce or quit gambling. The sample was weighted to match the gambling and demographic profile for the same subsample (i.e., past month gamblers) in a recent Canadian national survey. Results 5.7% reported that they tried to cutback or stop gambling in the past year. As predicted, individuals making a change attempt had greater levels of problem gambling severity and were more likely to have a gambling problem. Of individuals with problem gambling, 59.8% made a change attempt. Of those, 90.2% indicated that they did this primarily on their own, and 7.7% accessed formal or informal treatment. Most people attempting self- change indicated that this was a personal preference (55%) but about a third reported feeling too ashamed to seek help. Over a third (31%) reported that their attempt was successful. Of the small group of people accessing treatment, 39% described it as helpful. Conclusions Whereas gambling treatment-seeking rates are low, rates of self-change attempts are high. The public health challenge is to promote self-change efforts among people beginning to experience gambling problems, facilitate success at self-change by providing accessible support for use of successful strategies, and provide seamless bridges to a range of other treatments when desired or required.